(untitled) (Fiep Bulletin - online, 2020)
It is common knowledge that aging is a natural process that affects everything that has life, and obviously affects the human being greatly. With this, aging affects our body in many ways, physiologically, contributing to the slowdown of metabolism, decrease of neural capacity, psychologically, because life becomes more difficult, everything that was done with ease today becomes a war, from simple bathing to more complex activities, and physically the damage of age appears more clearly sarcopenia, which is the decrease in muscle mass, and osteopenia, which is the decrease in bone mass, contribute a lot to injuries, which often are caused by falls. That said, this paper aims to analyze the quality of life of a group of elderly people who practice physical activity regularly, through a questionnaire that includes several facets aimed specifically at the elderly population who practice these exercises, considering that physical activity It is an important weapon, not to combat aging, but to minimize its effects on our body. ?Among the results stand out the quality of life in qualitative form, where 6% have a life considered bad, 61% with regular quality of life and 33% just demonstrated to have a good quality of life.